2012
DOI: 10.1002/hyp.9320
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant effects on the water‐stable aggregation of wettable soils from the continental USA

Abstract: Surfactants may affect soil structure differently depending upon the soil or the quality of rainfall or irrigation water. This study examined whether the water‐stable aggregation of 11 wettable soils was affected by surfactants and the water in which the soils were sieved. The study also examined whether the wettable soils' water drop penetration time (WDPT) was affected by surfactants, water drop quality, and elapsed time since the surfactants were applied. Two nonionic surfactants and a surfactant‐free water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 75 publications
(118 reference statements)
0
2
0
Order By: Relevance
“…The water repellency of the original, air-dried organic materials was assessed through the use of water drop penetration time (WDPT) to explore potential repellency effects on water retention dynamics. We measured WDPT for organic materials via the technique described by Lehrsch (2013). Previous research has indicated that WDPT values of <1 s, 1 to 60 s, 60 to 600 s, and >3600 s correspond to the nonrepellent, slightly repellent, strongly repellent, and extremely repellent classes (Leelamanie et al, 2008;Devereux et al, 2012).…”
Section: Site Soils and Amendmentsmentioning
confidence: 99%
“…The water repellency of the original, air-dried organic materials was assessed through the use of water drop penetration time (WDPT) to explore potential repellency effects on water retention dynamics. We measured WDPT for organic materials via the technique described by Lehrsch (2013). Previous research has indicated that WDPT values of <1 s, 1 to 60 s, 60 to 600 s, and >3600 s correspond to the nonrepellent, slightly repellent, strongly repellent, and extremely repellent classes (Leelamanie et al, 2008;Devereux et al, 2012).…”
Section: Site Soils and Amendmentsmentioning
confidence: 99%
“…The decreasing Ca loads with increasing application rates of compost and manure (figures 2a and 2b, respectively) suggest that Ca was not present in excess in our runoff. The Ca concentrations in the amendments we applied ( ; as reported by Lehrsch [2013], for the nearly identical Rad soil) likely limited, though only to a slight degree, the P concentrations in our sprinkler irrigation runoff (Turner et al 2004) and, thereby, the DRP loads measured in our study (table 6). Moreover, our runoff 's Ca-an effective flocculating agent-may have decreased the runoff 's suspended sediment concentrations.…”
Section: Constituent Loads In Runoff (mentioning
confidence: 56%
“…King and Bjorneberg (2011) also found-like we did- (table 5), much variability in runoff among irrigations. They found that runoff from the Portneuf silt loam often increased with successive irrigations, likely due to decreasing infiltration as a consequence of a continually developing surface seal on this poorly structured soil (Lehrsch andKincaid 2001, 2006). That runoff did not vary with manure rates was also reported by Volf et al (2007).…”
Section: Resultsmentioning
confidence: 99%